2020
DOI: 10.1128/aem.02757-19
|View full text |Cite
|
Sign up to set email alerts
|

Factors Required for Adhesion of Salmonella enterica Serovar Typhimurium to Corn Salad (Valerianella locusta)

Abstract: Salmonella enterica is a foodborne pathogen often leading to gastroenteritis and is commonly acquired by consumption of contaminated food of animal origin. However, frequency of outbreaks linked to the consumption of fresh or minimally processed food of nonanimal origin is increasing. New infection routes of S. enterica by vegetables, fruits, nuts, and herbs have to be considered. This leads to special interest in S. enterica interactions with leafy products, e.g., salads, that are mainly consumed in a minimal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 76 publications
(59 reference statements)
8
24
0
Order By: Relevance
“…Alleles of bapA with deletions of BIg1, BIg28, or BIg1-28 were expressed by AHT induction. Synthesis and secretion of mutant forms of BapA were confirmed by flow cytometry in prior work (28), and revealed that deletion of BIg1-28 ablated surface expression of BapA. The deletion of BIg1 showed a similar significantly increased adhesion as observed before for full-length BapA, indicating no contribution of BIg1 in adhesion to lettuce.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…Alleles of bapA with deletions of BIg1, BIg28, or BIg1-28 were expressed by AHT induction. Synthesis and secretion of mutant forms of BapA were confirmed by flow cytometry in prior work (28), and revealed that deletion of BIg1-28 ablated surface expression of BapA. The deletion of BIg1 showed a similar significantly increased adhesion as observed before for full-length BapA, indicating no contribution of BIg1 in adhesion to lettuce.…”
Section: Resultssupporting
confidence: 67%
“…In a previous study (28) we deployed a reductionist, synthetic approach to identify factors that contribute to the surface binding of STM to leaves of corn salad. We now investigate factors that contribute to surface binding of STM to leaves of lettuce.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations